(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2023)
The use of synthetic antibiotics in medicine has encountered widespread resistance, prompting the development of new drugs from herbal plants. Herbal plants have the potential to become a new alternative to antibiotics. Turmeric is a plant that is widely used as a traditional medicine. Turmeric contains many secondary metabolites such as alkaloids, triterpenoids, flavonoids, tannins, and polyphenols, making it a potential traditional medicine, especially as an antibiotic. This research method aims to determine the chemical content of turmeric and determine its antibacterial activity. The research method involved extracting turmeric leaves with methanol, identifying the compounds using TLC, FT-IR, and GC-MS, and then testing their antibacterial activity. The results of TLC, FT-IR, and GC-MS measurements showed that the most abundant chemical compound in turmeric leaves was phytol. The results of the antibacterial activity inhibition of turmeric leaf extract showed that the methanol extract of turmeric leaves inhibited S. aureus and E. coli bacteria with values of 7.07 mm and 6.93 mm, respectively. This experiment indicates that the methanol extract of turmeric leaves has moderate antibacterial potential against S. aureus and E. coli bacteria.